(untitled) (Minerva, 2019)
The analysis of predicate frames (PF) is effective in studying support verb constructions (SVC): on the one hand, as a complement to the test of comparison between these structures and the corresponding simple verbs and, on the other, in relation to the predicative nature of the noun in these constructions and its argument structure. The nouns πόλεμος, μάχη, εἰρήνη are combined with the verb ποιέω in two different types of construction: with the middle voice forms they constitute a SVC, whereas with the active voice forms the verb acts as a full verb. This distribution may not be quite clear in the case of μάχην ποιέω.